Measuring the Burden of Pediatric Burn Injury for Parents and Caregivers. Issue 3 (May 2015) - Rimmer, Ruth Brubaker; Bay, R. Curt; Alam, Now Bahar; Sadler, Ian J.; Richey, Karen J.; Foster, Kevin N.; Caruso, Daniel M.; Rosenberg, David
<x xml:space="preserve">Abstract</x> This study sought to identify which commonly experienced burn-related issues parents/caregivers of burn-injured youth deemed most stressful, difficult, and disruptive during their child's initial acute burn care hospitalization, and following the child's discharge. Parents completed an 11-item survey, asking them to rate the difficulty of items regarding their child's burn injury. The scale was created by burn doctors, nurses, and psychologists with an average of 10.5 (SD ± 4.8) years of experience. Items selected were among common parental problems reported in the burn literature. Respondents included 69 parents/caregivers of previously hospitalized, burn-injured youth. The majority were mothers, n = 51 (74%), and n = 34 (49%) were Caucasian. The most represented age group was 37 to 45 years, n = 31 (45%). Children were on average, 6.04 years out from their initial injury. All parents reported their child's pain as the most difficult part of the injury, n = 69 (100%). The second most common issue was the child's first hospital stay. The other two items found to be "very hard" or "pretty hard" were the time spent away from their other children, and feelings of hopelessness in being unable to fix everything for their child. In this study, key parental problems occurred during the child's initial hospitalization. Burn staff cannot alleviate all problems, however, staff education regarding distressing problems faced by parents, as well as possible solutions, can be made available.